Conceptions of Sense of Humor in Psychology - R V Yershova; R Z Sharapova (Peoples' Friendship University of Russia (RUDN University), 2012)
The article gives a theoretical analysis of the modern psychological approaches to the problem of the nature and structure of the sense of humor as a personality quality and proves the necessity of the system-functional approach to perceiving the sense of humor as a personality property.